Fruitless decommissions regulatory elements to implement cell-type-specific neuronal masculinization. - Brovkina, M.V.; Duffié, R.; Burtis, A.E.C.; Clowney, E.J. (PLoS Genetics, 2021)
In the fruit fly Drosophila melanogaster, male-specific splicing and translation of the Fruitless transcription factor (FruM) alters the presence, anatomy, and/or connectivity of >60 types of central brain neurons that interconnect to generate male-typical behaviors. While the indispensable function of FruM in sex-specific behavior has been understood for decades, the molecular mechanisms underlying its activity remain unknown. Here, we take a genome-wide, brain-wide approach to identifying regulatory elements whose activity depends on the presence of FruM. We identify 436 high-confidence genomic regions differentially accessible in male fruitless neurons, validate candidate regions as bona fide, differentially regulated enhancers, and describe the particular cell types in which these enhancers are active. We find that individual enhancers are not activated universally but are dedicated to specific fru+ cell types. Aside from fru itself, genes are not dedicated to or common across the fru circuit; rather, FruM appears to masculinize each cell type differently, by tweaking expression of the same effector genes used in other circuits. Finally, we find FruM motifs enriched among regulatory elements that are open in the female but closed in the male. Together, these results suggest that FruM acts cell-type-specifically to decommission regulatory elements in male fruitless neurons.